Full-scale tests on composite concrete T-beams subjected to cyclic and monotonic loading. Issue 9 (17th August 2018) - Xue, Weichen; Hu, Xiang; Yang, Yunjun
Abstract : The composite T-beams investigated in this study consisted of precast concrete beams, precast concrete slabs and cast-in-place (CIP) slabs. Improvement measures were adopted in two types of the composite T-beams: additional tie bars located in semi-circular grooves were added for strengthening the connection of the precast concrete slabs and an inverted T-shape precast concrete beam was used for strengthening the flexural stiffness of precast beams. Nine full-scale tests were conducted under low reversed cyclic loading and positive and negative monotonic loading. The results showed that the composite T-beams failed in a flexural pattern that was similar to that of the control CIP T-beams. All the T-beams exhibited good energy dissipation capacity and small slip was measured in the composite T-beams. The flexural strength of the composite T-beams was about 7·5% lower than that of the CIP T-beams. The curvature ductility of the composite T-beams was more than 4·0 and about 13% lower than that of the CIP T-beams. Due to cumulative damage, the flexural strength and curvature ductility of all the T-beams under cyclic loading was about 30% and 40% lower than that under monotonic loading, respectively. The improvement measures used in this work were effective at ensuring good performance of composite T-beams.